Pemanfaatan Teknologi Informasi (IT) Bagi Siswa Sekolah Menegah Atas Negeri 6 Kabupaten Kepahyang - Yessi Mardiana; Toibah Umi Kalsum; Khairil Khairil; Reno Supardi; Dimas Aldi Romadoni (Jurnal Dehasen Untuk Negeri, 2023)
The development of technology requires a variety of activities that can be easily accessible regardless of time and space. The development of information technology becomes innovative, dynamic, and economically beneficial solutions. The information technology is an answer to the problems and challenges faced by the world of education. Cloud computing changes the way information technology services are provided and distributed, so that institutions have the opportunity to access educational and scientific information. Cloud computing is a computing model, where the resources such as processor or computing power, storage, network, and software become abstract and are provided as a service on a network or internet by using remote access patterns. The use of cloud computing based technologies in the learning process can enhance the efficiency and effectiveness in improving the quality of learning outcomes